Community Training On Distraction And Relaxation Techniques To Improve Nurses’ Competence At Guido Valadares National Hospital, Timor Leste - Norberto daCosta Abi; Antonia Soares; Rosa Paicheco; Adelina Ximenes Martin; Atik Setiawan W (Health Gate, 2026)
Background: Nurses play an essential role in implementing non-pharmacological pain management; however, the application of distraction and relaxation techniques in clinical practice remains limited due to insufficient knowledge and practical skills. Continuous professional development through structured training is needed to enhance nurses' competence and promote evidence-based nursing practice. Objective: This community service activity aimed to improve nurses' competence in applying distraction and relaxation techniques through a structured training program at Guido Valadares National Hospital (HNGV), Timor-Leste. Methods: This community service program involved 30 nurses who voluntarily participated in educational activities consisting of lectures, interactive discussions, demonstrations, and supervised practical sessions. Program evaluation was conducted using pretest and posttest questionnaires assessing knowledge, attitudes, practical skills, and clinical application. Descriptive analysis was used to summarize participants' competency levels, while the Wilcoxon Signed-Rank Test was applied to support the evaluation of competency changes before and after the training. Results: Prior to the training, most participants demonstrated poor competency (60.0%), whereas after the program, the majority achieved good competency (73.3%). The mean competency score increased from 58.50 ± 11.06 before training to 84.03 ± 9.63 after training. Statistical analysis showed a significant improvement in participants' competency following the implementation of the program (Z = −4.783; p < 0.001). Conclusion: The community service training program successfully improved participants' competencies in implementing distraction and relaxation techniques as non-pharmacological pain management interventions. The program may serve as a sustainable strategy for strengthening evidence-based nursing practice and improving the quality of nursing services at Guido Valadares National Hospital.